Determination of Qibla with the Help of the Sine Law - Spesaly Andar, Zarghoona (Journal of Natural Sciences – Kabul University, 2020)
This article discusses the achievements of mathematicians regarding spherical trigonometry before Abu Rayhan Mohammad bin Ahmad al-Biruni. Abu Rayhan Mohammad bin Ahmad al-Biruni made important contributions and obtained results that provided research methods for mathematicians in various fields. Using these results, mathematicians were able to develop methods for determining the direction of the Qibla and calculating the distance between two points on the Earth's surface. This article also reviews the achievements of al-Biruni, which have been examined by other mathematicians in various fields.